HUBUNGAN ANTARA IKLIM ORGANISASI DAN KOMUNIKASI INTERPERSONAL DENGAN PERILAKU AGRESIF PADA ANGGOTA SATUAN RESERSE KRIMINAL POLDA SUMATERA UTARA - Zulhafni Zulhafni; Suryani Hardjo (Analitika: Jurnal Magister Psikologi UMA, 2011)
Basically this study aims to Relationship Between Organizational Climate and Interpersonal Communication With Aggressive Behavior in Criminal Investigation Police Unit Member of North Sumatra. The study was conducted on 120 police officers at the Criminal Police Field. Based on the elaboration of the chapter the theoretical basis, the proposed hypothesis of the study, which reads. negative relationship between interpersonal communication with the aggressive behavior of police officers on the assumption that the better interpersonal communication, the lower the aggressive behavior of police officers.           In an effort to prove the third hypothesis above, we used data analysis methods Regression Analysis of Two Predictors, wherein the first predictor (independent variable I) is the organizational climate and the second predictor (independent variable II) is an interpersonal communication and the criterion (dependent variable / dependent) is aggressive behavior. Based on data analysis using regression analysis two predictors, the obtained results as follows: There is a significant negative relationship between organizational climate and interpersonal communication with aggressive behavior. This means that the better the organizational climate and komuunikasi received by members of the police, then the lower aggressive behavior. Conversely the climate is not good organization and communications received by members of the police, the higher the aggressive behavior is evidenced by the results of the correlation coefficient which Freg = 26.567 p <0.010. Thus, the hypothesis has been proposed in this study, been accepted.